Mapa de preferência e modelos mistos utilizados na análise sensorial afetiva de sais culinários - Abatti, Leticia Moreira (Universidade Federal de São Carlos, 2021)
Considering that salt is part of people's food routine and is essential for the proper functioning of the human body, but, especially when in excessive amounts, it can lead to negative consequences for the health of the population, product options that can lead to a decrease in the daily amounts of sodium consumed by people. Therefore, it is necessary to sensorially evaluate common, light and herbal salt, as to acceptance, choosing for this two statistical tools, internal preference maps and mixed models. Thus, for the sensory analysis, acceptability tests were applied for the aspects of general appearance, color, aroma and flavor, with 120 evaluators (60 men and 60 women). Thus, it was concluded that, in general, common salt had greater acceptability in all attributes, followed by light salt, which in many aspects was well accepted by evaluators. Herbal salt was the least accepted product in most sensory attributes. Still for both statistical instruments, the only attribute that showed a difference in the acceptance of evaluators according to gender was the general appearance. Still, a difference was noticed between the results obtained for the preference maps and the mixed model for the attributes: general appearance, color and flavor.
Preference map and mixed models used in affective sensory analysis of culinary salts
Keywords: Mapa de preferência; Modelo de regressão linear misto; Software R; Aceitação; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS